THE IMPACT OF SOCIAL MEDIA ADDICTION ON ACADEMIC PERFORMANCE AMONG UNIVERSITY STUDENTS - Khadijah Abdul Rahman,; Mohd Akmal Faiz Osman,; Wan Muhammad Zulfikri Wan Ya’acob,; Nur Shaliza Sapiai, (Journal of Islamic, Social, Economics and Development, 2023)
Social media has a huge impact on university student’s daily life. The usage of social media nowadays has varied ranging from socializing, to searching for information, learning something new, reading news, and finding products. However, the extent of social media use among university students has escalated towards addiction which needs to be investigated. By conducting a quantitative survey among university students at renowned public university in Malaysia, SPSS version 28 have been used to analyze the impact of social media addiction on academic performance hence the findings proved that social media addiction significantly affects students’ CGPA. The relationships between the impact of social media addiction and academic performance were analyzed using the correlations method. Several recommendations were made based on research findings to cater to this issue.